2021
DOI: 10.1002/clc.23688
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among random forest, logistic regression, and existing clinical risk scores for predicting outcomes in patients with atrial fibrillation: A report from the J‐RHYTHM registry

Abstract: Background Machine learning (ML) has emerged as a promising tool for risk stratification. However, few studies have applied ML to risk assessment of patients with atrial fibrillation (AF). Hypothesis We aimed to compare the performance of random forest (RF), logistic regression (LR), and conventional risk schemes in predicting the outcomes of AF. Methods We analyzed data from 7406 nonvalvular AF patients (median age 71 years, female 29.2%) enrolled in a nationwide AF registry (J‐RHYTHM Registry) and who were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Furthermore, the HAS-BLED score’s reliance on labile INR is outdated, given the shift towards DOACs 13 . Our findings of a modest improvement in ML performance over conventional risk scores align with prior studies 16,17 , which consistently demonstrated the poor performance of the HAS-BLED score, with AUC-ROC ranging from 0.50 to 0.64 16,19,20,44,45 . However, these studies were limited by their focus on broader contexts or specific AF subpopulations 18,19 , restricting their applicability to the broader AF population on DOACs in a real-world clinical scenario when first evaluated by a cardiologist for AF management.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the HAS-BLED score’s reliance on labile INR is outdated, given the shift towards DOACs 13 . Our findings of a modest improvement in ML performance over conventional risk scores align with prior studies 16,17 , which consistently demonstrated the poor performance of the HAS-BLED score, with AUC-ROC ranging from 0.50 to 0.64 16,19,20,44,45 . However, these studies were limited by their focus on broader contexts or specific AF subpopulations 18,19 , restricting their applicability to the broader AF population on DOACs in a real-world clinical scenario when first evaluated by a cardiologist for AF management.…”
Section: Discussionsupporting
confidence: 88%
“…CatBoost is commonly utilized in the fields of business (60), financial assessments (61), Medicare fraud detection (62), environmental science (63,64), and public science (36). According to our review of the literature, in the field of medicine, the random forest model has retained a competitive edge and is often superior in the prediction and classification of medical conditions compared with traditional logistic regression methods and machine learning methods such as neural networks, SVMs, and decision trees (65)(66)(67)(68). In our study, the CatBoost model outperformed the random forest model in classifying nonrecurrent and recurrent stroke.…”
Section: Discussionmentioning
confidence: 99%
“…LR utilizes a function of the logistic to create a binary dependent parameter [18]. It is a curve-fitting module in which the dependent value varies in relation to the independent value and the data points are aligned to be as close to the curve as possible [19], [20]. This study, the regularization was carried out with the help of ridge (L2), that reduces the sum of the weight's squares to the greatest extent possible.…”
Section: Logistic Regression (Lr)mentioning
confidence: 99%
“…This work proposed two cases for training and prediction process over three group's image eye diseases; Case 1, Utilised three models, ANN, LR, and KNN, separately for the training and testing process to distinguish the images of two eye diseases, CNV and DME, from the healthy one. Figure 2 illustrate the proposed algorithm for this case, which utilized (6,000) total images (with 2,000 images for each type of eye disease: CNV, DME, and healthy one were chosen for comparison), and the dataset was split into 9:1 ratio for training and testing (The ratio of training 90% with repeat train/test (20), get the highest AC (0.958) for ANN models). For case 2, a new model was presented and we called it the Stacking model.…”
Section: Proposed Algorithmsmentioning
confidence: 99%